Toxicity assessment of verapamil and its photodegradation products - Klementová, Šárka; Poncarová, Martina; Kahoun, David; Šorf, Michal; Dokoupilová, Eliška; Fojtíková, Pavla (Environmental science and pollution research international, 2020)
Pathways of photochemical degradation of a cardiovascular drug verapamil under conditions relevant to natural waters and the toxicity of the photoproducts to Daphnia magna were investigated. Photodegradation was shown to proceed via photocatalysed mechanism. Two main photodegradation pathways were recognised: the first leading to hydroxylation at the methylamino position followed by splitting of verapamil molecule into two fragments, and the second providing the main active metabolite of verapamil, norverapamil, and a series of norverapamil isomers, followed again by their splitting at the amino group position. Twenty-two products of photodegradation were identified. Toxicity assays in sublethal concentrations of the parental drug, of the photoproduct mixture, and of norverapamil revealed no direct negative response in Daphnia magna to verapamil. On the other hand, photochemical products significantly lowered the number of juveniles, number of clutches, and body size of Daphnia. The exposition of Daphnia to norverapamil showed the same but even more pronounced effects than its exposition to the mixture of photoproducts, which leads to the conclusion that norverapamil is mainly responsible for the toxicity of photoproduct mixture and represents a noteworthy threat to aquatic invertebrates.
Keywords: Photocatalysed degradation in aqueous solution; Water Pollutants, Chemical; Cardiovascular drugs; fotolýza; Daphnia magna; Animals; Verapamil; Daphnia; Photolysis; zvířata; verapamil; chemické látky znečišťující vodu; Chronic toxicity